Ginsenoside Rg1 regulating inflammatory response and bone-remodeling through Keap1/Nrf2 signaling pathway in rats with periodontitis - Yang Zhou; Yunan Zhang; Li Wang; Youbo Liu; Zhongke Wang; Ling Guo (Scientific Reports)
Abstract Periodontitis is a chronic inflammatory disease arising from local microorganisms and the host’s own aberrant immune regulation. Ginsenoside Rg1(GS-Rg1) is an active extract of ginseng known for its anti-inflammatory and osteogenesis effects. However, GS-Rg1 has not been shown to treat periodontitis and its exact mechanism remains elucidated. Orthodontic wires inoculated with Porphyromonas gingivalis were wrapped around the gingiva of the first molar in rats to induce periodontitis. Inflammatory factor secretion was analyzed using RT-PCR and immunohistochemistry. The number of osteoclasts and secretion of osteogenic factors were analyzed using TRAP staining and immunofluorescence. The destruction of periodontal tissues was evaluated using Micro-CT and H&E staining. Keap1/Nrf2 pathway protein expression was analyzed using Western-Blot and RT-PCR. Applying GS-Rg1 significantly reduced the secretion of inflammatory factors IL-6 and increased the secretion of transforming growth factor TGF-β1. Additionally, GS-Rg1 decreased osteoclast numbers and increased RUNX2 and OCN expression. Furthermore, GS-Rg1 was found to enhance the expression of the related protein Nrf2 while reducing Keap1 expression. GS-Rg1 may effectively alleviate periodontitis through the Keap1/Nrf2 pathway. In conclusion, our study provided the first preclinical evidence to support GS-Rg1 as a potential therapeutic agent for treating periodontitis.